2022
DOI: 10.1039/d2sc03375e
|View full text |Cite
|
Sign up to set email alerts
|

A platinum–ruthenium hybrid prodrug with multi-enzymatic activities for chemo-catalytic therapy of hypoxic tumors

Abstract: Regulation of tumor hypoxia and redox homeostasis is a promising strategy for cancer therapy. Nanocatalytic medicine has played more and more important roles in this field because it can cleverly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…According to the above results, the GPx-like activity of CuV 2 O 6 was caused by a redox change in the vanadium center. The redox valence changes of active centers have also been observed in other types of nanozymes, such as Mn-, 52 Cu-, 53,54 Ru-based, 55 etc. In some bimetallic nanozymes, both active sites would produce valence redox changes.…”
Section: Qiaochu Zhangmentioning
confidence: 83%
See 2 more Smart Citations
“…According to the above results, the GPx-like activity of CuV 2 O 6 was caused by a redox change in the vanadium center. The redox valence changes of active centers have also been observed in other types of nanozymes, such as Mn-, 52 Cu-, 53,54 Ru-based, 55 etc. In some bimetallic nanozymes, both active sites would produce valence redox changes.…”
Section: Qiaochu Zhangmentioning
confidence: 83%
“…[99][100][101][102] Recent reports revealed different active atoms in GPx-like nanozymes, including Au, Ce, Co, Fe, Mo, Pt, Ru, etc. 50,55,[103][104][105][106][107][108][109][110][111][112][113][114][115] For example, the widely studied SOD-and CAT-like CeO 2 is seldom reported for its GPx-like activity. A study undertaken in 2019 by Ming, Zhang, and co-workers showed that CeO 2 exhibited GPx-like activity and that single-atom Pt doping further increased the initial reaction rate from 15.89 to 22.07 µM min −1 (Fig.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative transition metal species are known to be able to perturb intracellular redox homeostasis and further strengthen oxidative stress, which may lead to cell death (44)(45)(46)(47)(48). Analogously, the sono-activated reduction of cyaninplatin, which can efficiently accumulate in the mitochondria, may also perturb the redox balance of cancer cells.…”
Section: Cellular Redox Homeostasis Disturbed By Cyaninplatinmentioning
confidence: 99%
“…[ 29–33 ] Among these nanozymes, ruthenium‐based biomaterials have been extensively used as nanozymes for biomedicine application, including tumor therapy, bacterial infection, and liver injury therapy. [ 34–37 ] For instance, Liu and co‐workers developed a Ru‐based metal–organic framework with multiple enzyme‐mimetic activities for alleviating inflammatory disease by scavenging ROS and reactive nitrogen species. [ 38 ] Therefore, ruthenium‐based biomaterials exhibit great potential for ischemic‐related diseases therapy.…”
Section: Introductionmentioning
confidence: 99%